PENINGKATAN KEMAMPUAN PENDIDIK PENDIDIKAN NONFORMAL DALAM IMPLEMENTASI PEMBELAJARAN - Nursam Nursam (Jurnal Ilmiah Visi, 2008)
The role of educator in non-formal education is essential to succeed the non-formal education programs. This article discusses some theoretical knowledge about learning and teaching to improve the educator’s competence. The writer believes that the educators in non-formal education will be able to improve their performance by implementing the theories discussed in this article.